1975
DOI: 10.1042/bj1500153
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthesis in the perfused liver of streptozotocin-diabetic rats

Abstract: 1. Net glycogen accumulation was measured in sequentially removed samples during perfusion of the liver of starved streptozotocin-diabetic rats, and shown to be significantly impaired, compared with rates in normal (starved) rats. 2. In perfusions of normal livers with glucose plus C3 substrates, there was an increase in the proportion of glycogen synthetase 'a', compared with that in the absence of substrates. This response to substrates, followed in sequential synthesis and enzymic sensitivity in the perfuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 55 publications
12
81
1
Order By: Relevance
“…First, fructose was administered to inhibit glycogen breakdown [28] and activate glycogenesis [29]. Addition of 4 mM fructose did not alter the GSH consumption caused by different agents but as expected it prevented their glycogenolytic effect and rather glycogen formation occurred (Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…First, fructose was administered to inhibit glycogen breakdown [28] and activate glycogenesis [29]. Addition of 4 mM fructose did not alter the GSH consumption caused by different agents but as expected it prevented their glycogenolytic effect and rather glycogen formation occurred (Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…Whereas, the treatment with plant extract as well as phytosynthesized AgNPs significantly improved the body weight loss. The TC and TG levels were retrieved comparable to normal group over a period of 21 days administration of AgNPs, the mechanism of preventing the muscle loss could probably attribute to reversal of antagonism [38].…”
Section: The Antidiabetic Activity Of Phytosynthesized Agnpsmentioning
confidence: 76%
“…Glycogen is therefore useful for providing a readily available source of glucose for the body. Whitton and Hems (1975) observed a decrease in liver glycogen in rat perfused with STZ and impairments in glycogen synthesis. Gardner, et.al, (1993) suggested that regulation of glucose-6-phosphatse by insulin plays a role in the suppression of hepatic glucose production during feeding.…”
Section: Resultsmentioning
confidence: 95%